TWO NEW SPECIES OF SPHAERULINA FROM INDIA - PANDE, ALAKA; RAO, V.G. (REINWARDTIA, 1998)
Two new species of the genus Sphaerulina (Ascomycetes-Dothideales) collected from India are described and illustrated here.